2008
DOI: 10.1128/iai.00072-08
|View full text |Cite
|
Sign up to set email alerts
|

EspF Interacts with Nucleation-Promoting Factors To Recruit Junctional Proteins into Pedestals for Pedestal Maturation and Disruption of Paracellular Permeability

Abstract: Many pathogenic bacteria subvert normal host cell processes by delivering effector proteins which mimic eukaryotic functions directly into target cells. EspF is a multifunctional protein injected into host cells by attaching and effacing pathogens, but its mechanism of action is not understood completely. In silico analyses of EspF revealed two key motifs: proline-rich domains and PDZ domain binding motifs. Such functional domains may allow EspF to act as an actin nucleation-promoting factor by mimicking host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 51 publications
5
63
0
Order By: Relevance
“…Moreover, EspF can cause actin sequestration and recruit junctional proteins, such as occludin, claudin, ZO-1 and ZO-2, to the pedestals, inducing the redistribution and loss of transepithelial electrical resistance, disruption of paracellular permeability and depolymerization of actin. Ultimately, this leads to EspF-induced TJ disruption [45]. Our study suggests that EspF may be involved in future science group www.futuremedicine.com the regulation of the actin cytoskeleton and TJs, which confirmed and extended previous findings that indicated the disruption of the TJ barriers might be associated with EspF's regulation of the actin cytoskeleton.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, EspF can cause actin sequestration and recruit junctional proteins, such as occludin, claudin, ZO-1 and ZO-2, to the pedestals, inducing the redistribution and loss of transepithelial electrical resistance, disruption of paracellular permeability and depolymerization of actin. Ultimately, this leads to EspF-induced TJ disruption [45]. Our study suggests that EspF may be involved in future science group www.futuremedicine.com the regulation of the actin cytoskeleton and TJs, which confirmed and extended previous findings that indicated the disruption of the TJ barriers might be associated with EspF's regulation of the actin cytoskeleton.…”
Section: Resultssupporting
confidence: 79%
“…The YFPn tag may alter the conformation or activity of the labeled protein, having an effect on the binding site on PRR1. Besides, the combination between N-WASP and EspF can be detected by coimmunoprecipitation at 1-1.5-h postinfection, but no interplay was found at 3-h postinfection [45]; this may also be one of the reasons why we did not screen N-WASP. It can be seen that the protein reads were not always proportional to the interaction strength, but it was influenced by the expression level of the protein itself; therefore, we set it as a preliminary criterion for protein interaction, not the gold standard.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains and plasmids used in this study are shown in Table 1. HeLa (ATCC CCL-2) and RK13 actin-GFP cells (Peralta-Ramirez et al, 2008) were maintained in D-MEM (Invitrogen) supplemented with 10 % (v/v) fetal calf serum (FCS, Eurobio) and 80 mg gentamicin ml 21 at 37 uC in 5 % CO 2 . G418 (Invivogen) was added at 400 mg ml 21 to RK13 actin-GFP cells.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, EspF is capable to disrupt the tight junctions proteins in intestinal epithelial cells (67), which could facilitate the release and dissemination of tumor cells, and contributing to metastasis of colon cancer. In addition, EPEC infection increased the expression of macrophage inhibitory citokine 1 (MIC-1), this molecule has been associated with an important increase on survival and spread of colon tumor cells in a GTPase RhoA dependent pathway (68).…”
Section: Entero Pathogenic Escherichia Coli and Colon Cancermentioning
confidence: 99%